Disequilibrium in Development Finance: The Contested Politics of Institutional Accountability and Transparency at the World Bank Inspection Panel. Issue 4 (19th June 2018) - Sovacool, Benjamin K.; Naudé Fourie, Andria; Tan‐Mullins, May
ABSTRACT: This article examines the dynamic nature with which independent accountability mechanisms operate. Focusing on the World Bank, the authors argue that its Inspection Panel evolves according to internal and external pressures. In seeking to achieve equilibrium, and protect its authority and independence, the Panel has gone through several distinct phases: negotiation, emergence, protracted resistance, assertion of independence and authority, renewed tension, and contestation. The core novelty of the article is its application of concepts from outside the field of development studies — notably institutional accountability from the governance literature, and judicialization from the legal studies literature — to the topic of the Inspection Panel. Examining the Panel in this way demonstrates that accountability mechanisms represent a hybrid of transnational governance influenced by a range of actors including project‐affected peoples, national governments, managers and development donors. Accountability in development finance is about competing interests as well as competing conceptions and expectations of accountability. In such a complex and multi‐scalar system, the Panel is not only concerned with delivering well‐researched investigation reports; it is also an entity seeking to ensure its own survival, as well as an arbiter of its own brand of legitimacy and accountability.